2021
DOI: 10.1016/j.ijnss.2020.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety culture and handoff evaluation of nurses in small and medium-sized hospitals

Abstract: Objectives This study was conducted to investigate the current status of handoffs, perception of patient safety culture, and degrees of handoff evaluation in small and medium-sized hospitals and identified factors that make a difference in handoff evaluation. Methods This is a descriptive study. 425 nurses who work at small and medium-sized hospitals in South Korea were included in our study. They completed a set of self-reporting questionnaires that evaluated demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
1
12
0
1
Order By: Relevance
“…The Ministry of Health and Welfare of South Korea has reinforced regulations on firefighting, infection prevention and patient safety for hospital facilities and stipulates “time‐out in the operating room” as an essential item for the evaluation of medical institutions (Korea Institute for Healthcare Accreditation, 2018 ). Nevertheless, it has been reported that this is not observed in some small‐ and medium‐sized hospital operating rooms (Kim et al., 2021 ; Park et al., 2016 ).…”
Section: Introductionmentioning
confidence: 94%
“…The Ministry of Health and Welfare of South Korea has reinforced regulations on firefighting, infection prevention and patient safety for hospital facilities and stipulates “time‐out in the operating room” as an essential item for the evaluation of medical institutions (Korea Institute for Healthcare Accreditation, 2018 ). Nevertheless, it has been reported that this is not observed in some small‐ and medium‐sized hospital operating rooms (Kim et al., 2021 ; Park et al., 2016 ).…”
Section: Introductionmentioning
confidence: 94%
“…Nurses caring for patients in obstetric units will benefit from a standardized unit-specific hand-off structure. Kim, Lee and Kim [7] conducted a descriptive study including 425 nurses at small and medium sized hospitals in South Korea. Awareness of the existence of hand-offs and their effect on patient safety were evaluated.…”
Section: Nurses' Views Of Bedside Hand-offmentioning
confidence: 99%
“…Results showed that most nurses who experienced errors in hand-offs had no structure for hand-offs at their hospitals. Establishing structures for hand-offs, including the use of the electrical medical record and a standardized checklist of criteria for discussion between nurses at crucial hand-off points, including relief breaks and shift changes, could alleviate hand-off errors [7].…”
Section: Nurses' Views Of Bedside Hand-offmentioning
confidence: 99%
“…Small and medium‐sized hospitals with 100–400 beds in South Korea play an essential role in the provision of domestic healthcare services, and their nursing systems and staff structures differ from those in large hospitals (Korean Hospital Association, 2017). Small and medium‐sized hospitals can experience serious patient safety issues related to nursing staff shortages, insufficient education opportunities, and a lack of initiative to improve the quality of nursing (Kim et al, 2020). It is therefore important to understand the experiences of and difficulties faced by nurses preparing for and performing handovers in small and medium‐sized hospitals.…”
Section: Introductionmentioning
confidence: 99%